Propagation of torsional surface waves in a non-homogeneous half-space with circular irregularity in free surface - Sethi, M.; Sharma, A.K.; Sharma, A. (Zielona Góra: Uniwersytet Zielonogórski)
The present paper studies the effect of circular regularity on propagation of torsional surface waves in an elastic non-homogeneous half-space. Both rigidity and density of the half-space are assumed to vary inversely linearly with depth. Separation of variable method has been used to get the analytical solutions for the dispersion equation of the torsional surface waves. Also, the effects of non-homogeneity and irregularity on the phase velocity of torsional surface waves have shown graphically.
Keywords: non-homogeneous media; torsional waves; rigidity; irregularity